Cognitive sex differences in effects of music in Wisconsin Card Sorting Test. (March 2020) - Feizpour, Azadeh; Parkington, Helena C.; Mansouri, Farshad A.
Recent studies suggest that females and males show different levels of susceptibility to neuropsychological disorders which might be related to sex differences in executive control of behaviour. Music, as a cognitively salient factor, might influence cognitive functions; however, it is unclear how sex and music interact in influencing executive control of behaviour in a dynamic environment. We tested female and male participants in a computerized analogue of the Wisconsin Card Sorting Test (WCST) while listening to music or in silence. We found that music decreased the percentage of correct trials in both sexes. While music decreased response time in females, it had an opposite effect in males. Response time increased in error trials (error slowing), and music sex-dependently influenced error slowing. Conflict between potential rules adversely influenced performance in the current trial (conflict cost) in both sexes and listening to music increased conflict cost. These findings suggest that music shows both adverse and beneficial effects on various behavioural measures in the WCST, some of which are sex-dependent. Our findings suggest that in using music as an adjunct for rehabilitation of neuropsychological disorders, both adverse and beneficial effects and sex dependency need to be considered.